OTC Medication use during exams among undergraduates: Insights from a Nigerian Institution - Ogbodu , Olubunmi Margaret (Journal of Ecohumanism, 2025)
Exam period and academic success are associated with high stress levels which necessitates the use of over-the-counter (OTC) medication by university students as a coping strategy. The study investigated factors influencing OTC use among undergraduates during examination periods in Nigeria. A cross-sectional study was conducted and data was collected using a 22-item questionnaire from 386 undergraduate students. Data was analysed using the Statistical Package for Social Science (SPSS) 23 revealing painkillers, cough and cold medications, and vitamins as commonly used medications. Results suggest an association between family income, gender, level of study, age, and OTC medication use. The study concludes that the use of OTC medication as a self-medication practice is prevalent among undergraduates during the exam periods. Inadequate information about the adverse reactions and related interactions of OTC medications could lead to adverse health consequences. Study recommendations to policymakers include interventions on university campuses to incorporate factors that promote and sustain the rational use of medications and encourage routine public health campaigns on the dangers of medication misuse to form a part of the orientation program for new students and throughout the semester. These measures are particularly, important during exam periods when an increase in academic stress is experienced.